P_ω-closedness and its Generalization With Respect to a Grill - Basu, C. K.; Afsan, B. M. Uzzal (Sarajevo Journal of Mathematics, 2024)
In this paper, a new kind of covering axiom pre-ω-closedness (P_ω-closedness, for short), stronger than p-closedness due to J. Dontchev et. al. [7] is introduced in terms of pre-ω-open sets [16]. Several characterizations via filter bases and grills [23] along with various properties of this concept are obtained. Grill generalizations of P_ω-closedness and associated concepts have also been investigated. 2000 Mathematics Subject Classification. 54D20, 54D25, 54D99, 54A20